Secrecy, anonymity and confidentiality in blood donors with HIV - Hokama, Newton Key [UNESP]; Bonequini Junior, Pedro [UNESP]; Hokama, Paula de Oliveira Montandon [UNESP] (FapUNIFESP (SciELO), 2021)
A recent article published in this journal on confidentiality in the care of HIV/aids patients reports that, in the event of a positive result in the Screening Tests for the virus, the Blood Bank must, in addition to disposing of the blood bag, refer the donor to the reference service. Due to the implicit ethical dilemmas we have experienced, this led us to a detailed review of the respective brazilian legislation and critical analysis of the issue. People with HIV/aids are surrounded by prejudices, discrimination and negative social repercussions, so it is essential that the Blood Bank professional who will communicate this news is fully aware of the issues involving secrecy and confidentiality, and fully trained and capable to proceed adequately. We present and discuss the fundamental points of the current Brazilian legislation the theme and how we must communicate to the donor about the detection of HIV serodiagnosis.
Secreto, anonimato y confidencialidad de los donantes de sangre con VIH
Sigilo, anonimato e confidencialidade de doadores de sangue com HIV
Keywords: Blood donors; Confidentiality; HIV seroprevalence